Continuous and Placement Assessment Results as a Predictor of Student Achievement in Primary Schools - Tolera Danki Negassa; Samuel Asnake (‎‎‎TAZKIYA Journal of Psychology, 2023)
The purpose of this study was to explore the performance of out-of-school children in speed school and accelerated learning programs as a basis for success in primary schools. This research field has received very little attention. The continuous assessment and placement test results of students at risk were not used much in the literature, which this study aims to fill. The total number of students involved in the study was 624. The study used the continuous assessment average scores and placement test scores as predictor variables. The results show that the relationship between placement test and 1st-semester score in grade four was significant, r (196) = .501, p < .001. For the Accelerated Learning Program, the placement test and 1st-semester score in grade three were significant, r (111) = .413, p<.001. As a tool to forecast primary school students' future achievement, the teacher-made continuous assessment appears to be less useful than placement tests for children who come through speed school. Students from speed school backgrounds performed better than students from formal schools; students from accelerated learning program backgrounds performed almost similarly to students from formal schools except in environmental science. The study indicated that in grade four of formal primary school, continuous assessment was found to be poorly linked with student knowledge and skills. However, the results show that both comparisons found placement examinations to be a reliable indicator of children's achievement in primary schools. It can be concluded that students who joined grades three and four of formal school through speed school and an accelerated learning program are capable of achieving minimum learning competence in the subsequent educational outcomes in elementary grades.